NSAIDs and COVID-19: A New Challenging Area - Hananeh Baradaran; Hadi Hamishehkar; Haleh Rezae (Tabriz University of Medical Sciences, 2020)
Considering the recent controversies regarding the use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) in Coronavirus disease 2019 (COVID-19) patients, and due to the limited published data in this field, we reviewed currently available evidence for the use of NSAIDs in viral respiratory tract infections to help make decisions in this area. Currently, there is insufficient evidence to judge the safety and efficacy of NSAIDs in patients with COVID-19. According to the current evidence, acetaminophen is the choice treatment for symptomatic relief. If the patients' symptoms are not controlled by acetaminophen, naproxen may be used as an alternative therapy.